Peran Pemerintah Menanggulangi Radikalisme dan Terorisme Di Indonesia - Siti Aminah (Balitbangda Provinsi Lampung, 2016)
Radicalism and terrorism have caused a national security crisis. This paper aims is to describe factors have caused radicalism and terrorism and formulate the steps taken by the government to eradicate radicalism and terrorism in Indonesia. Qualitative approach is used to answer the questions proposed in this study. The result of this research shows that there were multiple factors that caused radicalism and terrorism. From the perspective of social and political, radicalism arises because of the dominance of a system and the large discrepancy in the community, giving rise to fatalism. Sociological perspective, the trigger radicalism is the identity crisis that happened in the younger generation, moral shock and ideological differences and social networks. Trigger from an economic perspective is the economic inequality that cause social jealousy. The role of the Government to tackle radicalism and terrorism through the efforts: strengthening of policies, strengthening institutions of formal education, structuring media utilization, changes in the pattern of de-radicalization, improve the community economy and pursuing a strategy of prevention through early detection.